A study to assess future academic career and service plan of house surgeons - Manjunath, M.; Biradar, Mallikarjun K.; Lankeshwar, Suresh (International Journal Of Community Medicine And Public Health, 2018)
Background: No healthcare without a workforce has been a universal truth. However, shortages and misdistribution of the qualified healthcare workforce have become global concerns affecting nearly all countries, especially less-developed countries. Methods: Cross sectional study done on house surgeons in AIMS, BG Nagar, Mandya district, involving 178 house surgeons. Simple proportions were used to analysis the data. Results: Out of 178 house surgeons, 177 (99.4%) had plan for future academic career and service. 158 (88.7%) had plan for PG course and 19 (10.6%) planned for general practice, 80 (94%) planning to do super specialization and 84 (47.1%) plan to teach in medical colleges. Majority of house surgeons 161 (91.4%) have expressed to work in urban area and 17 (9.5%) in primary health centre in rural areas. Conclusions: Almost all the house surgeons have planned well in advance about their future academic and career plan.